The Cognitive Behavioral Counseling (CBT) Model Based On Tri Kaya Parisduha Philosophy - Kadek Suranata (Department of Guidance and Counseling, FIP, Undiksha, 2020)
Cognitive-behavioral counseling (CBT) is a counseling model development that has widely proven evidence of its feasibility and effectiveness in various settings. This model has developed rapidly and is integrated with various compatible concepts. One of them is integrated with the values or philosophies that developed in society or endogenous values. Tri Kaya Parisudha is one of the philosophies and values of local wisdom which is a reference in the life of the Hindu community, especially in Bali, Indonesia. The values contained in Tri Kaya Parisudha have high relevance and are integrated with the concepts and procedures of CBT. This study describes the meaning of counseling and the stages of CBT which are the basis for the development of the Tri Kaya Parisudha-based philosophy. This counseling model is oriented towards efforts to train the people to understand and implement good thinking (rational), good saying (normative), and well being (adaptive), to develop thoughts, feelings ( emotions)) and healthy behavior. The role of the counselor, as well as the main stages and procedures of this counseling model, include (1) the formation of a counseling relationship, (2) the assessment stage, (3) implementation technique, (4) evaluation, and (5) ) termination. This study has implications for the development of a counseling model that is oriented towards the revitalization of local wisdom values. The results of this study are open to researchers who are interested in further examining this concept. The results of empirical research are needed that prove how effective this model is in various life settings.